Pendidikan profesi guru (PPG) pariwisata - Woro Priatini (Inovasi Kurikulum, 2020)
The tourism sector generates foreign exchange for the country. In its development, there are a number of challenges and obstacles. Likewise, the education sector has the same conditions. For this reason, it is necessary to carry out a Tourism Professional Teacher Education (PPG) program that has competencies covering attitudes, knowledge and professional skills of teachers. The academic activities of the first semester are workshops on developing learning tools, presentations of the results of developing learning tools, and peer teaching, as well as deepening or strengthening material in the field of study/skills. The second semester academic activities are in the form of Field Experience Practice (PPL), Classroom Action Research (PTK), and for vocational PPG, there are practical activities in industry. With this program, it is hoped that PPG Tourism will provide pedagogic mastery and special tourism expertise programs.   Abstrak Sektor pariwisata menghasilkan devisa bagi negara. Dalam perkembangannya, terdapat sejumlah tantangan dan hambatan. Demikian pula, sektor pendidikan mempunyai kondisi yang sama. Untuk itu, perlu dilakukan program Pendidikan Profesi Guru (PPG) Kepariwisataan memiliki kompetensi meliputi Sikap, Pengetahuan dan Keterampilan Keprofesian Guru. Kegiatan akademik semester pertama lokakarya pengembangan perangkat pembelajaran, presentasi hasil pengembangan perangkat pembelajaran, dan peer-teaching, serta pendalaman atau penguatan materi bidang studi/keahlian. Kegiatan akademik semester kedua berupa Praktik Pengalaman Lapangan (PPL), Penelitian Tindakan Kelas (PTK), dan bagi PPG kejuruan ada kegiatan praktik di industri. Dengan program tersebut, diharapkan PPG Pariwisata memberikan penguasaan pedagogik, dan program keahlian khusus kepariwisataan. Kata kunci: Guru Pariwisata; Pariwisat;, Pendidikan Profesi Guru (PPG)